Comparative Analysis of Hemagglutination Inhibition and Plaque Reduction Neutralization Tests for Japanese Encephalitis Virus Antibody Detection - Cui Li; Jianqing Wan; Deli Wang; Lu Xiao; Xuni Li; Cunshuai Zhang; Zhao Wang (Viruses)
Japanese encephalitis (JE) is a zoonotic disease caused by the Japanese encephalitis virus (JEV), belonging to the Flaviviridae family. Diagnosis of Japanese encephalitis (JE) based on clinical signs alone is challenging due to the high proportion of subclinical cases. The Plaque Reduction Neutralization Test (PRNT) is considered the gold standard for detecting JE-specific antibodies because of its high specificity. However, PRNT is complex, time-consuming, and requires live viruses, limiting its applicability in routine diagnostics. In this study, we compared the sensitivity and correlation of the Hemagglutination Inhibition (HI) assay and PRNT for detecting JE antibodies in avian serum samples. We conducted a comparative analysis of the outcomes obtained from the PRNT and HI using 240 serum samples collected from 30 JEV-immunized avian subjects at various time points. Comparative analysis revealed a significant correlation between the HI and PRNT (R2 = 0.9321, p ≤ 0.0001). The Bland–Altman analysis also exhibited favorable concordance between the two assays. Consequently, HI may function as a viable substitute for PRNT in the screening of a substantial number of serum samples.